Reading and Annotating Galen between 1515–1531: on some Latin Galen Editions in the Library of the Carmelites in Cracow - Koźluk, Magdalena (Studia Ceranea, 2019)
Copies of early-printed books have been of interest to to-day’s collectors and researchers not only for their material aspects (names of publishers and places of printing, fonts and composition, number of known copies etc.), but also because they bear signs of their often erratic history following their publication. The path followed by a particular copy of an early-printed book is reflected in its general state as an object (for instance the state of its binding), but also in its internal aspect. On the pages of a copy of an early-printed book, annotations, drawings doodles or graphics testify to the intimate relationship that its owners entertained with it. To better understand how owners dealt with copies of the books they possessed, this paper examines the annotations found in copies of some books that belong to the Carmelite convent in Cracow. We hope to bring to the attention of scholars, copies of works of Galen housed in this library, and primarily to set a perspective on how books were read by cultured individuals of in the 16th century period. To do so, we analyse copies of the 1507 Venice edition of the Articella and a copy of Latin edition of Galien (Iuntae, Venice, 1531). We attempt to identify the intellectual perspectives from which cultured readers approached such texts in the 16th century.